LINGKUNGAN KERJA, BUDAYA ORGANISASI DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI SMP ISLAM TERPADU PERMATA HATI BANJARNEGARA - Siti Maesaroh; Ulfa Marselina (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2021)
ABSTRACT Every company needs an organization. Important factors that can affect the performance of these employees can be a work problem, work environment and work culture of the workplace. This study aims to determine whether the work environment, cultural organization, and workload are related to the performance of employees at SMP IT Permata Hati Banjarnegara. This study uses quantitative by collecting primary data obtained by requesting questionnaires to employees. The population data used is the population of individuals and teachers of SMP IT Permata Hati Banjarnegara numbering 40 people with the sample used is a saturated sample so that the total number of research samples is there. The results showed a positive and significant work environment on the performance of SMP IT Permata Hati Banjarnegara. Organizational Culture does not have a positive and significant effect on the performance of SMP IT Permata Hati Banjarnegara. Positive and significant workload on the performance of employees at SMP IT Permata Hati Banjarnegara. The work environment, organizational culture and workload have a significant influence on employee performance.